2023
DOI: 10.1200/jco.22.01742
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Young Adults With Cancer Is Associated With Medicaid Expansion Through the Affordable Care Act

Abstract: PURPOSE Medicaid expansion through the Affordable Care Act (ACA) has been shown to improve insurance coverage and early diagnosis of cancer in young adults (YAs); whether these improvements translate to survival benefits remains unknown. We examined the association between Medicaid expansion under the ACA and 2-year overall survival among YAs with cancer. METHODS Using the National Cancer Database, we identified 345,413 YAs (age 18-39 years) diagnosed with cancer in 2010-2017. We applied the difference-in-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…44,49,50 Two NCD analyses, applying a difference-in-difference approach, examined stage of disease at diagnosis and survival in Medicaid expansion versus nonexpansion states. 49,50 During 2011-2016, Medicaid expansion states demonstrated greater shifts to earlier-stage disease at diagnosis, including improvements among non-Hispanic Black AYAs. 50 Subsequently (2010-2017), survival benefits were best for those with higher-stage disease at diagnosis, and among racial and ethnic minoritized populations ( v non-Hispanic White).…”
Section: The Role Of Insurance Ses and The Aca In Aya Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…44,49,50 Two NCD analyses, applying a difference-in-difference approach, examined stage of disease at diagnosis and survival in Medicaid expansion versus nonexpansion states. 49,50 During 2011-2016, Medicaid expansion states demonstrated greater shifts to earlier-stage disease at diagnosis, including improvements among non-Hispanic Black AYAs. 50 Subsequently (2010-2017), survival benefits were best for those with higher-stage disease at diagnosis, and among racial and ethnic minoritized populations ( v non-Hispanic White).…”
Section: The Role Of Insurance Ses and The Aca In Aya Outcomesmentioning
confidence: 99%
“…50 Subsequently (2010-2017), survival benefits were best for those with higher-stage disease at diagnosis, and among racial and ethnic minoritized populations ( v non-Hispanic White). 49…”
Section: The Role Of Insurance Ses and The Aca In Aya Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study of over 345,000 AYA patients with cancer, two-year overall survival was higher in patients treated in states that expanded Medicaid access through the Affordable Care Act compared with those in states without expansion (net increase of 0.55 percentage points). 2 These data support the importance of increased access to health insurance for AYA cancer survivors.…”
mentioning
confidence: 76%
“…Following the implementation of the ACA in 2014, 40 states and the District of Columbia adopted the Medicaid expansion provision of the ACA so far, and 10 states chose not to expand Medicaid, creating a natural experiment for evaluating whether and to what extent Medicaid expansion affects health care access and health outcomes. Previous studies have shown that individuals residing in expansion states who receive a new diagnosis of cancer are more likely to have health insurance coverage, present with early disease stage at the time of diagnosis, and have better overall survival than individuals residing in nonexpansion states …”
Section: Introductionmentioning
confidence: 99%